2005
DOI: 10.1128/jb.187.14.4774-4781.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitous Protein Domain EAL Is a Cyclic Diguanylate-Specific Phosphodiesterase: Enzymatically Active and Inactive EAL Domains

Abstract: The EAL domain (also known as domain of unknown function 2 or DUF2) is a ubiquitous signal transduction protein domain in the Bacteria. Its involvement in hydrolysis of the novel second messenger cyclic dimeric GMP (c-di-GMP) was demonstrated in vivo but not in vitro. The EAL domain-containing protein Dos from Escherichia coli was reported to hydrolyze cyclic AMP (cAMP), implying that EAL domains have different substrate specificities. To investigate the biochemical activity of EAL, the E. coli EAL domain-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
527
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(543 citation statements)
references
References 26 publications
9
527
1
6
Order By: Relevance
“…The levels of c-di-GMP are also controlled by c-di-GMP phosphodiesterases (PDEs) that contain a conserved EAL domain (4). A number of proteins contain both of these domains, suggesting they may be bifunctional enzymes with opposing activities, although the EAL domains of these presumptive bifunctional proteins tend to be more divergent and perhaps inactive (5).…”
Section: Analysis Of Pseudomonas Aeruginosa Diguanylate Cyclases and mentioning
confidence: 99%
“…The levels of c-di-GMP are also controlled by c-di-GMP phosphodiesterases (PDEs) that contain a conserved EAL domain (4). A number of proteins contain both of these domains, suggesting they may be bifunctional enzymes with opposing activities, although the EAL domains of these presumptive bifunctional proteins tend to be more divergent and perhaps inactive (5).…”
Section: Analysis Of Pseudomonas Aeruginosa Diguanylate Cyclases and mentioning
confidence: 99%
“…Although the biological pathways through which c-di-GMP regulates persistence, cell aggregation and the switch to the commensal lifestyle are currently poorly understood, the proteins responsible for c-di-GMP synthesis and degradation have been determined and, at least partially, characterized. Bacterial diguanylate cyclase (DGC) activity is found in GGDEF domain-containing proteins (Paul et al, 2004;Ryjenkov et al, 2005;Hickman et al, 2005;Kulesekara et al, 2006), whilst EAL domain-containing proteins have been shown to have c-di-GMP-specific phosphodiesterase (PDE) activity (Bobrov et al, 2005;Christen et al, 2005;Schmidt et al, 2005;Kulesekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The only known effector domain that synthesizes c-di-GMP (designated as diguanylate cyclase activity, DGC) is the GGDEF domain. Two domains, EAL and HD-GYP, hydrolyze c-di-GMP (designated as phosphodiesterase activity, PDE) into linear 5Ј-phosphoguanylyl-(3Ј-5Ј)-guanosine (pGpG) or guanosine monophosphate (GMP), respectively (7)(8)(9)(10)(11)(12)(13). Many DGC proteins also contain an RxxD conserved motif 5 amino acids upstream from the GGDEF motif.…”
mentioning
confidence: 99%